Professor Brian Bosworth. A brief biography - Elizabeth Baynham (Universitat Autònoma de Barcelona. Departament de Ciències de l’Antiguitat i l’Edat Mitjana., 2018)
Brief biographical profile of prof. A. B. Bosworth.